Mechanism of long-term strength retrogression of silica-enriched Portland cement assessed by quantitative X-ray diffraction analysis - Qin, Jiankun; Pang, Xueyu; Li, Hailong; Zhang, Zhen (Frontiers in Materials, 2022)
In order to clarify on the driving force of cement long-term strength retrogression, a comprehensive quantitative X-ray diffraction (XRD) analysis were conducted on silica-enriched (60%-80% by weight of cement) cement samples set and cured under the condition of 200 °C and 50 MPa with a maximum duration of 180 days. The phase content evolution with time was determined by three different methods on the average of three specimens: the external standard method; the partial or no known crystal structure (PONKCS) method; and the hybrid method. Although the specific phase content estimated by different methods varied slightly, the overall trend of change of all phases were similar. The phase transformation in set cement at high temperature condition is dependent on the slurry composition. In silica-deficient system, tobermorite and amorphous C-S-H were transformed to xonotlite; while in silica-sufficient system, tobermorite and amorphous C-S-H were transformed to gyrolite. These phase transformations involve gradual structural changes of cement hydration products, which may be the driving force of long-term strength retrogression. However, such structural changes can only be detected by XRD once the transformation is complete.